Computational study of a single-phase flow in packed beds of spheres - Gunjal, P. R.; Ranade, V. V.; Chaudhari, Raghunath V. (AICHE Journal, 2005)
Packed-bed reactors are widely used in petrochemical, fine chemical, and pharmaceutical industries. Detailed knowledge of interstitial flow in the void space of such packed-bed reactors is essential for understanding the heat and mass transfer characteristics. In this paper, fluid flow through the array of spheres was studied using the unit-cell approach, in which different periodically repeating arrangements of particles such as simple cubical, 1-D rhombohedral, 3-D rhombohedral, and face-centered cubical geometries were considered. Single-phase flow through these geometries was simulated using computational fluid dynamics (CFD). The model was first validated by comparing predicted results with published experimental and computational results. The validated model was further used to study the effect of particle arrangement/orientation on velocity distribution and heat transfer characteristics. The simulated results were also used to understand and to quantify, relative contributions of surface drag and form drag in overall resistance to the flow through packed-bed reactors. The model and the results presented here would be useful in elucidating the role of microscopic flow structure on mixing and other transport processes occurring in packed-bed reactors. (C) 2005 American Institute of Chemical Engineers.
Keywords: CFD; drag; heat transfer; packed bed; packing arrangement

Dynamics of drop impact on solid surface: experiments and VOF simulations - Gunjal, P. R.; Ranade, V. V.; Chaudhari, Raghunath V. (AICHE Journal, 2005)
The process of spreading/recoiling of a liquid drop after collision with a flat solid surface was experimentally, and computationally studied to identify the key issues in spreading of a liquid drop oil a solid surface. The long-term objective of this study is to gain an insight in the phenomenon of wetting of solid particles in the trickle-bed reactors. Interaction of a falling liquid drop with a solid surface (impact, spreading, recoiling, and bouncing) was studied using a high-speed digital camera. Experimental data oil dynamics of a drop impact on flat surfaces (glass and Teflon) are reported over a range of Reynolds numbers (550-2500) and Weber numbers (2-20). A computational fluid dynamics (CFD) model, based on the volume of fluid (VOF) approach, was used to simulate drop dynamics on the flat sufaces. The experimental results were compared with the CFD simulations. Simulations showed reasonably good agreement with the experimental data. A VOF-based computational model was able to capture key features of the interaction of a liquid drop with solid surfaces. The CFD simulations provide information about finer details of drop interaction with the solid surface. Information about gas-liquid and liquid-solid drag obtained from VOF simulations would be useful for CFD modeling of trickle-bed reactors. (C) 2004 American Institute of Chemical Engineers.
Keywords: CFD; drop impact; recoiling; spreading; trickle bed; VOF

Gas-liquid flow generated by a Rushton turbine in stirred vessel: CARPT/CT measurements and CFD simulations - Khopkar, A. R.; Rammohan, A. R.; Ranade, V. V.; Dudukovic, M. P. (Chemical Engineering Science, 2005)
In this work, computer-automated radioactive particle tracking (CARPT), computed tomography (CT) and computational fluid dynamic (CFD) based models were used to investigate gas-liquid flow generated by a Rushton turbine. CARPT and CT measurements were carried out in a gas-liquid stirred vessel operating in two different flow regimes and captured the quantitative Eulerian information of gas-liquid flow. The CARPT data was then used to extract the circulation tune distribution in a vessel. A two-fluid model along with the standard k-epsilon turbulence model was used to simulate the dispersed gas-liquid flow in a stirred vessel. Appropriate drag corrections to account for bulk turbulence (along the lines proposed by Brucato et al. (Chem. Eng. Sci. 45(1998) 3295)) were developed to correctly simulate different flow regimes. The computational snapshot approach was used to simulate impeller rotation and was implemented in the commercial CFD code, FLUENT4.5 (of Fluent. Inc., USA). Most model predictions compared favourably with CARPT and CT measurements. Validated CFD models as attempted in this paper are promising to simulation of industrial stirred vessels. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: CARPT; CFD; CT; gas-liquid flow; stirred vessel

CFD simulation of mixing in tall gas-liquid stirred vessel: role of local flow patterns - Khopkar, A. R.; Kasat, Gopal R.; Pandit, A. B.; Ranade, V. V. (Chemical Engineering Science, 2006)
In this work, we have used the computational fluid dynamics (CFD)-based models to investigate the gas-liquid flows generated by three down-pumping pitched blade turbines. A two-fluid model along with the standard k-epsilon turbulence model was used to simulate the dispersed gas-liquid flow in a stirred vessel. Appropriate drag corrections to account for bulk turbulence [Khopkar and Ranade, 2005. CFD simulation of gas-liquid flow in a stirred vessel: VC, S33 and L33 flow regimes. A.I.Ch.E. Journal, accepted for publication] were developed to correctly simulate different flow regimes. The computational snapshot approach was used to simulate impeller rotation and was implemented in the commercial CFD code, FLUENT4.5 (of Fluent. Inc., USA). The computational model has successfully captured the flow regimes as observed during experiments. The particle trajectory simulations were then carried out to examine the influence of the different flow regimes on the circulation time distribution. The model predictions were verified by comparing the predicted results with the experimental data of [Shewale and Pandit, 2006. Studies in multiple impeller agitated gas-liquid contactors. Chemical Engineering Science 61, 489-504]. The computational model and results discussed in this study would be useful for explaining the implications local flow patterns on the mixing process and extending the applications of CFD models for Simulating large multiphase stirred reactors. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: CFD; Flow regimes; mixing; pitched blade turbine; stirred vessel

CFD simulation of shortstopping runaway reactions in vessels agitated with impellers and jets - Dakshinamoorthy, D.; Khopkar, A. R.; Louvar, J. F.; Ranade, V. V. (Journal of Loss Prevention in the Process Industries, 2006)
Runaway reactions are continuing to be a problem in the chemical industry. A recent study showed that 26% of our major chemical plant accidents are due to runaways. The consequences of runaway reactions are usually mitigated with (a) reliefs and containment systems or (b) shortstopping (reaction inhibition). This study covers the concept of shortstopping. One of the major reasons for runaways is power failure. In the advent of a power failure, mixing an inhibiting agent with the reactor contents is challenging. However, jets or impellers driven by a small generator can be used for mixing. This study compares shortstopping results in vessels agitated with jets and impellers using computational fluid dynamics (CFD). A commercial CFD code, Fluent is used. For shortstopping systems relying on jet mixing, angle and diameter of jet nozzle and jet velocity are the key design/operating parameters. For the systems with impellers, type, size and RPM of impeller are the key parameters. In this work, mixing with a jet mixer is first investigated for three nozzle diameters and two angles of injection. The best jet mixer configuration on the basis of mixing time is used for shortstopping studies. The simulated shortstopping results with the jet mixer are then compared with those obtained with impeller (Rushton and pitched blade turbine) stirred vessels. Our results identify the conditions for effective shortstopping; i.e., agitation requirements, locations for adding the inhibitor, and the quantity of inhibitor. The distribution of excess inhibitor is shown to be an important and essential design criterion for effective shortstopping when using impeller stirred vessels. The comparative study with a single jet shows that jet mixer is ineffective when used for shortstopping. Efforts such as adding excess inhibitor and inhibition with higher reaction rates at the same power, proved to be ineffective when using jet mixer compared to the results with impellers. (C) 2006 Elsevier Ltd. All rights reserved.
Keywords: CFD; impeller stirred vessels; jet mixer; runaway reaction; shortstopping

CFD simulation of liquid-phase mixing in solid-liquid stirred reactor - Kasat, Gopal R.; Khopkar, A. R.; Ranade, V. V.; Pandita, A. B. (Chemical Engineering Science, 2008)
A comprehensive CFD model was developed to gain an insight into solid suspension and its implications on the liquid-phase mixing process in a solid-liquid stirred reactor. The turbulent solid-liquid flow in a stirred reactor was simulated using a two-fluid model with the standard k-epsilon. turbulence model with mixture properties. The multiple reference frames (MRFs) approach was used to simulate impeller rotation in a fully baffled reactor. The computational model with necessary sub-models was mapped on to a commercial solver FLUENT 6.2 (of Fluent Inc., USA). The predicted solid concentration distribution was compared with the experimental data of Yamazaki et al. [ 1986. Concentration profiles of solids suspended in a stirred tank. Powder Technology 48, 205-216]. The computational model was then further extended to simulate and understand the implications of the suspension quality on liquid-phase mixing process. The computational model and the predicted results discussed here will be useful for understanding the liquid-phase mixing process in stirred slurry reactors in various stages of solid suspension. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: CFD; mixing; solid suspension; stirred reactor

Flow pattern in vortex diode: experiments and CFD simulations - Kulkarni, Amol A.; Ranade, V. V.; Rajeev, R.; Koganti, S. B. (AICHE Journal, 2008)
Vortex diodes are used as leaky nonreturn valves in applications, where it is desirable to avoid valves with moving parts. Despite their use in practice for several decades, no detailed analysis of the flow inside the vortex diodes is available. A strategy was derived for the CFD simulations of the vortical flow in diodes. A good agreement was seen between pressure drop (Delta P) across the inlet-outlet ports from CFD simulations, and the experimental data for five diode sizes. The simulations showed that in the reverse flow situation tangential velocity was dominant and resulted in conservation of angular momentum in the chamber until it reaches the axial exit port. This vortical motion induced a significant pressure drop (Delta P-r). The axial velocity gradient over the chamber cross-section helps in inducing relaminarization of the flow. In the forward flow mode, the fluid gets distributed radially over the chamber and exits through the tangential port, yielding low Delta P-f. The analysis showed that the performance of a diode is strongly affected by diode geometry, size, aspect ratio, nozzle configuration and Reynolds number. Among different configurations, the nozzles with entry port size equal to diode yielded higher diodicity. Simulations showed that using angle of divergence for diffuser sections of nozzles of the order of 7 degrees exhibited higher diodicity than smaller angles. It was also observed that at higher flow rates significantly higher diodicity was obtained using axial nozzles with larger radius of curvature for expander section. The modeling methodology and results presented will be useful for evolving better designs of vortex diodes.
Keywords: CFD; Diodicity; pressure drop; relaminarization; Vortex diode

Drying of almonds II: multiple particles - Chilka, A. G. (Indian Chemical Engineer, 2017)
Computational modelling is an efficient and effective tool for modelling the drying process for food products. Developing validated computational models for drying processes is essential to build energy-efficient drying units, producing uniform quality of dried products. This work presents drying behaviour of almonds with a specific focus on understanding interaction among multiple almonds. Eight (2 × 2 × 2) particles and twenty seven (3 × 3 × 3) particles arranged in the shape of a cuboid were used to conduct drying experiments in a Mettler Toledo Moisture Analyzer unit. Experiments were conducted to measure the moisture loss data with respect to drying time using almond kernels. Experimental data were used to understand drying kinetics as well as variation in moisture content with respect to their positions in a cuboid. Computational fluid dynamics based simulations were carried out for the flow, heat transfer and drying of particles in the unit. Actual geometry of individual particles was considered in simulations to predict the variation in velocity, heat and mass transfer coefficients for all the particles. Simulations predicted moisture loss data that matches well with the experimentally measured values. Average moisture for each layer was also compared for various intermediate drying times. Simulation results captured the overall drying process for multiple particles system adequately. The results are compared with the results obtained with drying of a single almond. The approach, models and presented results will be useful for designing large-scale drying units for almonds. © 2017 Indian Institute of Chemical Engineers
Keywords: Almonds; CFD; Drying

Estimation of gas induction in jet loop reactors: influence of nozzle designs - Sharma, D.V. (Chemical Engineering Research and Design, 2017)
Jet loop reactors are used widely for conducting gas liquid reactions because of the high mass transfer achieved in the gas–liquid ejector. Studies have shown that the mass transfer has a very strong correlation to the amount of gas induced in the ejector, and hence it is important to understand gas induction to enhance the performance of any gas–liquid nozzle. In this work, we used a single phase CFD model of the ejector with one adjustable parameter for estimating gas induction rates. After establishing that the model adequately describes the experimental data, the model was used for a quick evaluation of ejector geometries. Influence of key geometric parameters of gas–liquid ejectors like nozzle diameter, mixing tube length, distance between the nozzle outlet and mixing tube, suction chamber geometry and diffuser angle was investigated. It was found that dependence of gas induction on geometric parameters like distance between nozzle—mixing tube, suction chamber geometry, diffuser angle was either weak or had a clear maxima at or beyond a certain value of the geometric parameter. Other parameters like mixing tube length and nozzle diameter have a more complex impact on gas induction. The presented approach and results will be useful for quantifying influence of nozzle designs on gas induction rate in jet loop reactors.
Keywords: CFD; Gas Induction; Jet Loop Reactors; Nozzle Geometry